Determining the best graft‐sealant combination for skull base repair using a soft tissue in vitro porcine model. Issue 3 (25th October 2012) - Fandiño, Marcela; Macdonald, Kristian; Singh, Devin; Whyne, Cari; Witterick, Ian
Abstract : Background: The purpose of this work was to compare the absolute breaking strength of various soft tissue skull base (SB) repairs in an in vitro porcine model. Methods: A burst pressure (BP) testing system was designed using an axial loading force to create increasing hydraulic pressure. Defects measuring 0.5 × 0.5 cm were created in fascia lata samples. Defects were repaired using various grafts (pericranium and 2 different dural substitutes, Alloderm® and Durasis®) measuring 1.0 × 1.0 cm to cover the deficient area. Grafts were further reinforced onto the fascia background with either fibrin glue (Tisseel®) or hydrogel sealant (DuraSeal™). Each combination of graft and sealant was conducted 6 times and tested 24 hours after the repair. Results: The mean BP (±standard deviation [SD]) were as follows: DuraSeal™‐Alloderm, 12.5 ± 5.8 mmHg; DuraSeal™‐Durasis, 21.8 ± 20.7 mmHg; DuraSeal™‐pericranium, 44.7 ± 30.1 mmHg; Tisseel‐Alloderm, 30.6 ± 26.3 mmHg; Tisseel‐Durasis, 15.8 ± 18.6 mmHg; and Tisseel‐pericranium, 95.5 ± 86 mmHg. One‐way analysis of variance showed that the strongest type of repair was Tisseel‐pericranium when adjusting for the others ( p < 0.0001). The difference in mean BP of repair with DuraSeal™ vs Tisseel® was not statistically significant ( p = 0.22). Comparing sealants, the use of Alloderm® or Durasis® decreased the strength of the repair in comparison to pericranium ( p < 0.0001). Bonferroni analysis showed a significant difference between pericranium and Alloderm® ( p < 0.05) and between pericranium and Durasis® ( p < 0.05) but not between Alloderm® and Durasis® ( p > 0.05). Conclusion: In this model, the strongest type of repair (pressure 6 times higher than normal intracranial pressure) was the combination of Tisseel®‐pericranium. Our data will help guide surgeons who repair SB defects to choose the best graft and sealant.